2022
DOI: 10.3758/s13414-022-02587-z
|View full text |Cite
|
Sign up to set email alerts
|

Motivation by reward jointly improves speed and accuracy, whereas task-relevance and meaningful images do not

Abstract: Visual selection is characterized by a trade-off between speed and accuracy. Speed or accuracy of the selection process can be affected by higher level factors—for example, expecting a reward, obtaining task-relevant information, or seeing an intrinsically relevant target. Recently, motivation by reward has been shown to simultaneously increase speed and accuracy, thus going beyond the speed–accuracy-trade-off. Here, we compared the motivating abilities of monetary reward, task-relevance, and image content to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…3C, two sample t-test analysis, p < 0.001). One potential explanation is that participants became less motivated when they were prompted to switch their reaching movements from a high- to low-reward targets, since motivation is correlated with expected reward [18, 19]. To assess whether the longer SRT is due to the reduction of the expected reward, we recruited 6 participants to perform a modified version of the switch task.…”
Section: Resultsmentioning
confidence: 99%
“…3C, two sample t-test analysis, p < 0.001). One potential explanation is that participants became less motivated when they were prompted to switch their reaching movements from a high- to low-reward targets, since motivation is correlated with expected reward [18, 19]. To assess whether the longer SRT is due to the reduction of the expected reward, we recruited 6 participants to perform a modified version of the switch task.…”
Section: Resultsmentioning
confidence: 99%
“…This supports delay aversion being described as expressing negative affectivity 48 —typically associated with higher levels of anxiety and/or depression 51 . Longer reflection times have also been found to be associated with lower motivation to do tasks as instructed 52 , which higher conduct problems can reflect via non-compliance with external expectations. However, including the CGT parameters that correlated with social problems and the problem scores of conduct behavior and anxiety/depression in the same regression models, showed that none of them specifically predicted higher conduct or anxiety/depression problems.…”
Section: Discussionmentioning
confidence: 99%